2015
DOI: 10.1037/h0101061
|View full text |Cite
|
Sign up to set email alerts
|

Looking more and at different things: Differential gender eye-tracking patterns on an irony comprehension task.

Abstract: Irony is a well-studied figurative form of communication that requires the interpretation of the pragmatic aspects of language and ability to infer another’s mental state. Currently, the models that have been created to explain the process of verbal irony are not unanimous, which could be because of the choice of stimulus materials (written and auditory sentences). In real-life situations, a verbal irony statement is placed in a social context with multiple sources of cues that help integrate the correct meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…However, only a few studies have examined gender differences in the comprehension of sarcasm, and most have failed to find evidence for gender differences (Baptista, Macedo, & Boggio, 2015; see also Holtgraves, 1997). However, it has been suggested that the processing strategies used to understand irony might differ between men and women (Baptista et al, 2015) and that women might be better in recognizing sarcasm (Rothermich & Pell, 2015). Thus, the potential gender effects should be taken into account in the future.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…However, only a few studies have examined gender differences in the comprehension of sarcasm, and most have failed to find evidence for gender differences (Baptista, Macedo, & Boggio, 2015; see also Holtgraves, 1997). However, it has been suggested that the processing strategies used to understand irony might differ between men and women (Baptista et al, 2015) and that women might be better in recognizing sarcasm (Rothermich & Pell, 2015). Thus, the potential gender effects should be taken into account in the future.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Other researchers looked at individual differences in eye movements between male and female readers (Yang et al, 2014). Gender differences have been found in visual attention (Huang et al, 2014), discourse bias for pronoun interpretation (Arnold, 2015), exploratory eye movements of normal subjects (Miyahira et al, 2000), eye-tracking patterns in an irony comprehension task (Baptista et al, 2015) and eye movements in solving text-and-diagram science problems (Huang and Chen, 2015). In addition, the word frequency effect is also widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown an advantage for girls in emotion perception and in tasks requiring the identification of social intentions (Bosacki, 2000; Hughes & Dunn, 1998; Lee, 2013; McClure, 2000; McDonald et al, 2015). Research on gender differences has yielded mixed findings (e.g., Baptista, Macedo, & Boggio, 2015; Holtgraves, 1997; Rothermich & Pell, 2015); although some research has shown that males and females are equally capable of understanding nonliteral speech (e.g., Baptista et al, 2015; Holtgraves, 1997), other research has shown there are dissimilarities (e.g., Rothermich & Pell, 2015). Moreover, Baptista and colleagues (2015) demonstrated that although there were no gender differences in the comprehension of irony, female participants spent more time fixating on an ironic comic and take more time to understand the situation compared to males.…”
Section: Introductionmentioning
confidence: 99%
“…Research on gender differences has yielded mixed findings (e.g., Baptista, Macedo, & Boggio, 2015; Holtgraves, 1997; Rothermich & Pell, 2015); although some research has shown that males and females are equally capable of understanding nonliteral speech (e.g., Baptista et al, 2015; Holtgraves, 1997), other research has shown there are dissimilarities (e.g., Rothermich & Pell, 2015). Moreover, Baptista and colleagues (2015) demonstrated that although there were no gender differences in the comprehension of irony, female participants spent more time fixating on an ironic comic and take more time to understand the situation compared to males. Thus, we expect that some of the variance in our study can be explained by gender differences, which also was observed in a study of young adults using the same video database (Rothermich & Pell, 2015).…”
Section: Introductionmentioning
confidence: 99%